Atmospheric Plasma‐Assisted Deposition and Patterning of Natural Polymers. Issue 17 (6th May 2022) - Arkhangelskiy, Artem; Quaranta, Alberto; Motta, Antonella; Yang, Yuejiao; Yadavalli, Vamsi K.; Maniglio, Devid
Abstract: Plasma‐assisted deposition is a facile, yet sophisticated method to form biocompatible coatings on materials and introduce specific surface interactions. The plasma process provides unique features such as surface activation, functionalization, and assisted polymerization, all of which can be obtained under low power and room temperature conditions. Plasma‐assisted deposition can further provide coatings with enhanced adhesion and stability. Here, it is reported for the first time, a method for the controlled plasma deposition of the versatile biomaterial chitosan on a range of substrates – soda‐lime glass, metal alloy (Ti4Al6V), thermoplastic polymer (polyethylene terephthalate), and silicone rubber (poly(dimethylsiloxane)). The deposited chitosan films are characterized by atomic force microscopy, scanning electron microscopy and Fourier transform infrared spectroscopy, and evaluated for adhesion and stability. The proposed method is also successfully optimized for the deposition of multiple layers of different biomaterials. Specifically, coatings comprising alternate chitosan and silk fibroin layers are realized, together with patterned surfaces with programmable surface composition. The biological response of the chitosan‐on‐fibroin and fibroin‐on‐chitosan surfaces with and without patterning are investigated using cell culture experiments. Selective area deposition enables the development of improved surface finishes for biomedical devices. Abstract : The possibility of obtaining alternate layer‐by‐layer coatings of natural biopolymers via atmospheric plasma deposition is reported, enabling the production of patterned surfaces with programmable surface composition. The low power and non‐wet process provide optimal adhesion and growth control of different biomaterial layers, with minimal effect on intrinsic polymer structure, but with a significant impact on the control and guidance of cell behavior.